Density dependence influences competition and hybridization at an invasion front. Issue 5 (9th February 2021) - Wood, Connor M.; Kryshak, Nick; Gustafson, Michaela; Hofstadter, Daniel F.; Hobart, Brendan K.; Whitmore, Sheila A.; Dotters, Brian P.; Roberts, Kevin N.; Keane, John J.; Sawyer, Sarah C.; Gutiérrez, Rocky J.; Peery, M. Zachariah
Abstract: Aim: Landscape and climatic change are promoting range shifts, potentially leading to competition and hybridization between formerly isolated species. However, density‐dependent interactions can impede the timely identification of associated conservation problems. The barred owl's expansion into the spotted owl's range provides a natural experiment to test for density dependence in niche overlap and hybridization in the early versus late stages of a biological invasion, thus illuminating an important biogeographical process. Location: Pacific Northwest, USA to the northern Sierra Nevada, California, USA. Methods: In the northern Sierra Nevada, where barred owl density was low, we quantified niche overlap between barred owls and spotted owls along three axes (landscape‐scale habitat selection based on passive acoustic survey data, foraging habitat selection measured with GPS tag data, and diet measured with stable isotopes) and assessed hybridization with phenotypic data. We then compared our findings to studies on these species from the Pacific Northwest, where barred owl density is high. Results: In the Sierra Nevada, overlap in landscape‐scale habitat selection was low (spotted owl sites also occupied by barred owls: 21%), overlap in foraging habitat selection and diet was high (Pianka's niche overlap: 0.802; stable isotope ellipse overlap: 0.52), and hybridization was common (hybrid:barred owl ratio: 0.364). In the Pacific Northwest, niche overlap was high (barred owl occupancy of spotted owl territories: 40%–95%, Pianka's niche overlap of foraging habitat selection and diet: 0.809 and 0.429) and hybridization was rare (hybrid:barred ratio: 0.061). Main conclusions: Foraging habitat selection and diet were density‐independent and therefore predictive of the competitive exclusion of spotted owls in the Pacific Northwest that has resulted from the barred owl invasion. Landscape‐scale monitoring programmes capable of yielding systematic data on multiple species can offer an early warning of biological invasions; however, individual‐level traits such as foraging habitat selection may influence the population processes that can determine the outcome of those invasions.